Factors Affecting Financing of Rural Agricultural Projects in Rwanda: Experience of Equity Bank - Kayijamahe Chantal, Mukandoli (International Journal of Scientific Research and Management (IJSRM), 2021)
In the processes of financial deepening in low-income countries, lags prevail in the provision of services in the rural areas, particularly in the supply of the financial services required for agricultural activities and of those demanded by households that earn an important portion of their incomes from crops. This study examined factors affecting financing of rural agricultural projects in Rwanda with a focus on the experience of Equity Bank. Objectives were to assess how nature of existing financial products by Equity Bank influences financing of rural agricultural project in Rwanda; to examine how nature of rural agricultural projects in Rwanda influence access to Equity Bank’s financial services; to assess how characteristics of rural clients who engage in agricultural projects in Rwanda influence their ability to access Equity Bank’s financial services; and to examine influence of how rural agricultural environment in Rwanda influences ability of farmers to access Equity Bank’s financial services. Results revealed that there was a positive and significant relationship between factors influencing financial support and rural agricultural projects (rho=0.392, p value